2019
DOI: 10.1002/pc.25229
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of process‐induced deformations of double‐curved carbon–epoxy composite elements

Abstract: The process‐induced deformations constitute a severe obstacle to composite part designing and manufacturing. Therefore, in the present work, a method of geometric compensation of those deformations is presented. The compensation process starts with the development of a calculation method which allows to calculate the deformations with the use of Finite Element Method. Linear elastic material model is used in the calculations. Then, the calculated deformations are used to design the compensated geometry of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The result showed that the dimensional precision of the part could be significantly improved by the new compensation process. In recent years, with the development of computer aided engineering (CAE) supporting part development process technology, a new solution for mold profile compensation has been provided 104–106 . For example, Kappel et al 104 used the results of simulated deformation with morphing features available in the CATIA computer aided design (CAD) environment, which allowed the updating of the nominal geometry in the CAD surface model based on information describing deformation behavior, and then the information is transferred to the new CAD model via a text file.…”
Section: Deformation Control Strategies and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that the dimensional precision of the part could be significantly improved by the new compensation process. In recent years, with the development of computer aided engineering (CAE) supporting part development process technology, a new solution for mold profile compensation has been provided 104–106 . For example, Kappel et al 104 used the results of simulated deformation with morphing features available in the CATIA computer aided design (CAD) environment, which allowed the updating of the nominal geometry in the CAD surface model based on information describing deformation behavior, and then the information is transferred to the new CAD model via a text file.…”
Section: Deformation Control Strategies and Methodsmentioning
confidence: 99%
“…By comparison, it is found that the process‐induced distortions of the boxes could be reduced drastically based on the new compensation technology. On the other hand, the research team 106 used the linear elastomeric material model to calculate the geometry for the profile compensation design. By compensating the hyperbolic fragments on the leading edge of the composite wing, the results showed that the deformation was reduced by about 77%.…”
Section: Deformation Control Strategies and Methodsmentioning
confidence: 99%
“…For composites with the same material system, curing process, and surface treatment, the mold-part interaction relationship can be considered to be the same. 8,11 Since this article assumes that the interaction layer parameters are only related to the fiber orientation of the layup fabric in contact with the mold and ignores the interactions of the intermediate layups, the shear layer model established in this article can predict the warpage deformation of the layup composite with 0 layup on both the upper and lower surfaces. Therefore, in this section, [0/90/90/0] and [0/45/45/0] laminated composites are studied to verify the correctness of the model interaction parameters by comparing the simulated and experimental warpage deformation.…”
Section: Model Validationmentioning
confidence: 99%
“…In addition, Zhang et al 10 also reviewed that the stretching effect of the mold surface on the fabricated part is an important factor affecting the warpage of the plate in the curing process. And Galinska et al 11 believed that if the tool is not manufactured from the carbon–epoxy composite material, its thermal expansion is a significant factor that causes additional deformations.…”
Section: Introductionmentioning
confidence: 99%
“…Their utilization in modern vehicles, buildings, and airplanes is growing rapidly. [1][2][3][4][5] A significant characteristic of composite parts in the manufacturing process is the unavoidable cure-induced deformation. The deformation form of composite parts mainly includes two types: spring-in and warping.…”
Section: Introductionmentioning
confidence: 99%